PENGENALAN PEMBANGKIT LISTRIK TENAGA SURYA DI KOMUNITAS PEMBERDAYAAN DAMAI SEJAHTERA KELURAHAN BITOWA - Kamolan, Aries; Sampebatu , Limbran (Nindikayla Institute, 2025)
Power outages from PLN in turn in the city of Makassar in 2023 have greatly disrupted community activities. One of the communities affected by this policy is the Prosperous Peace Empowerment Community. Secretariat of the Peace Empowerment Community. The Secretariat of the Prosperous Peace Empowerment Community is located in Bitowa Village, Manggala District, Makassar City. This community is a partner in the current service. They come from mothers whose concentration of activities is the provision of snacks such as tempeh chips, donuts and other snacks. The Damai Sejahtera Empowerment Community in carrying out its activities is highly dependent on electricity resources for mixers and spinners. If the electricity supply does not exist or an outage from PLN occurs, their activities will also stop. As a result, their income can be reduced because their productivity is reduced. This community only knows that the source of electrical energy comes from PLN, so if PLN goes out, their business will also stop. To take advantage of their free time interrupted by their daily activities, it is very good to fill it with activities that provide additional knowledge about the field of electrical engineering, especially those related to energy supply such as Solar Power Plants (PLTS). With this knowledge, they get another alternative for energy supply so that their business is not disrupted when there is a power outage from PLN. This activity went well. Although there were not too many members who attended the implementation of the activity, they were very enthusiastic to know about solar power generators. They even hope that there will still be similar activities for their colleagues who have not had time to attend this activity. More than that, they hope to get assistance from solar PV equipment